Assessment of the Psychosocial Care Center multidisciplinary team from users' and family members' perspective - Jéssica dos Santos Pini; Paula Antunes Bezerra Nacamura; Camila Harmuch; Maria Antonia Ramos Costa; Bianca Cristina Ciccone Giacon-Arruda; Cremilde Aparecida Trindade Radovanovic; Maria Aparecida Salci; Marcelle Paiano (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to assess the multidisciplinary team of a Psychosocial Care Center I from users' and family members' perspective. Methods: an evaluative study, anchored in the fourth generation evaluation theoretical-methodological framework, carried out in a Psychosocial Care Center I, from September 2021 to March 2022. Eleven users and 06 family members participated. Data were collected through non-participant observation, individual interviews and negotiation sessions, and analyzed using the Constant Comparative Method, using the MAXQDA software. Results: the team develops its care based on individual and collective care, with integrated and complementary work by professionals. They seek to facilitate treatment initiation and continuation, considering health needs and offering support, understanding and guidance to users and their families. Final Considerations: the multidisciplinary team's work is based on the psychosocial paradigm, which can qualify care and strengthen the service role in the mental health network.